2007
DOI: 10.1021/bi701411g
|View full text |Cite
|
Sign up to set email alerts
|

Magic-Angle Spinning Solid-State NMR Spectroscopy of Nanodisc-Embedded Human CYP3A4

Abstract: Cytochrome P450 (CYP) 3A4 contributes to the metabolism of approximately 50% of commercial drugs by oxidizing a large number of structurally diverse substrates. Like other endoplasmic reticulum-localized P450s, CYP3A4 contains a membrane-anchoring N-terminal helix and a significant number of hydrophobic domains, important for the interaction between CYP3A4 and the membrane. Although the membrane affects specificity of CYP3A4 ligand binding, the structural details of the interaction have not been revealed so fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 64 publications
2
92
0
2
Order By: Relevance
“…While the de novo determination of a cytochrome P450 structure by NMR methods has not been reported, it has been shown that extensive sequential resonance assignments (a prerequisite for structure determination) can be made for soluble P450s (5), and high-quality solid state NMR spectra have been demonstrated for membrane-associated mammalian P450s as well (51). NMR methods often require a significant investment of time and resources to reach the point at which interpretable atomic resolution information concerning structure and dynamics of P450 can be obtained: Isotopically labeled samples must be prepared of sufficient concentration and purity for spectroscopy, a variety of multidimensional NMR experiments performed, and then sequential assignments must be made.…”
Section: Nuclear Magnetic Resonance As a Probe Of Cytochrome P450mentioning
confidence: 99%
See 1 more Smart Citation
“…While the de novo determination of a cytochrome P450 structure by NMR methods has not been reported, it has been shown that extensive sequential resonance assignments (a prerequisite for structure determination) can be made for soluble P450s (5), and high-quality solid state NMR spectra have been demonstrated for membrane-associated mammalian P450s as well (51). NMR methods often require a significant investment of time and resources to reach the point at which interpretable atomic resolution information concerning structure and dynamics of P450 can be obtained: Isotopically labeled samples must be prepared of sufficient concentration and purity for spectroscopy, a variety of multidimensional NMR experiments performed, and then sequential assignments must be made.…”
Section: Nuclear Magnetic Resonance As a Probe Of Cytochrome P450mentioning
confidence: 99%
“…However, combined with selective and uniform isotopic labeling, recent developments in solid-state NMR methods promise to make eukaryotic P450s more accessible (51,124). Using solid state NMR, the McDermott group has shown that substrate binding and spin state in CYP102 is temperature dependent, suggesting substrate reorientation as a function of temperature in that enzyme (48,49).…”
Section: Nuclear Magnetic Resonance As a Probe Of Cytochrome P450mentioning
confidence: 99%
“…Unlike other systems such as liposomes or detergent micelles, nanodiscs are relatively monodisperse (∼100 Å in diameter) and stable. Furthermore, protein-nanodisc complexes have proven to be easy to construct, are readily purified and concentrated, and are applicable to single particle structural analysis (5). We have now succeeded in assembling PA-pore lipidnanodisc and PA-pore:vesicle complexes and have reconstructed the nanodisc/vesicle-inserted PA pore by using EM of negatively stained specimens.…”
mentioning
confidence: 99%
“…In particular, solution NMR can report not only on protein tertiary structure, but also on conformational dynamics which are important to the interaction with protein partners (Lampe et al, 2008(Lampe et al, , 2010). An additional advantage is that protein NMR can be performed in the presence of lipid bilayer mimetics, such as bicells (Ahuja et al, 2013) or nanodiscs (Kijac et al, 2007;Gluck et al, 2009), allowing the investigator to examine the effect of lipid on protein-protein interactions. Protein NMR has been most widely used to examine interactions between CYP enzymes and their electron transfer partners (Ahuja et al, 2013;Estrada et al, 2013Estrada et al, , 2014Estrada et al, , 2016.…”
Section: Nuclear Magnetic Resonance (Nmr)mentioning
confidence: 99%